CD28-mediated costimulation impacts on the differentiation of DC vaccination-induced T cell responses - Voigt, H (Blackwell Science Inc, 2006)
Costimulatory signals such as the ones elicited by CD28/B7 receptor ligation are essential for efficient T cell activation but their role in anti-tumour immune responses remains controversial. In the present study we compared the efficacy of DC vaccination-induced melanoma specific T cell responses to control the development of subcutaneous tumours and pulmonary metastases in CD28-deficient mice. Lack of CD28-mediated costimulatory signals accelerated tumour development in both model systems and also the load of pulmonary metastases was strongly increased by the end of the observation period. To scrutinize whether lack of CD28 signalling influences priming, homing or effector function of Trp-2(180−188)/K(b)-reactive T cells we investigated the characteristics of circulating and tumour infiltrating T cells. No difference in the frequency of Trp-2(180−188)/K(b)-reactive CD8(+) T cells could be demonstrated among the cellular infiltrate of subcutaneous tumours after DC vaccination between both genotypes. However, the number of IFN-γ-producing Trp-2-reactive cells was substantially lower in CD28-deficient mice and also their cytotoxicity was reduced. This suggests that CD28-mediated costimulatory signals are essential for differentiation of functional tumour-specific CD8(+) T-effector cells despite having no impact on the homing of primed CD8(+) T cells.